Damage evolution and failure modes of coal-concrete composites with varying height ratios under cyclic loading - Renbo Gao; Fei Wu; Cunbao Li; Chunfeng Ye; Qingchuan He; Heping Xie (International Journal of Mining Science and Technology)
To ensure the safe implementation of underground reservoirs in abandoned coal mines, this study explores the mechanical behavior and failure mechanisms of coal-concrete composite structures under staged cyclic loading. Specimens with coal-to-concrete height ratios ranging from 0.5:1 to 3:1 were tested, with damage evolution continuously monitored using acoustic emission techniques. Results indicate that while the peak strength of pure materials decreases by approximately 1 MPa under cyclic stress compared to uniaxial compression, composite specimens exhibit strength enhancements exceeding 5 MPa. However, the peak strength of composite specimens decreases with increasing coal height, from 30 MPa at CR0.5 to 20 MPa at CR3.0. The damage state was assessed using the dynamic elastic strain energy index and Felicity ratio, which revealed that composite specimens are more prone to early damage accumulation. Spatial acoustic emission localization further reveals distinct failure modes across specimens with varying height ratios. To elucidate these differences, interfacial effects were incorporated into a modified twin-shear unified strength theory. The refined model accurately predicts the internal strength distribution and failure characteristics of the composite structures. These findings provide a theoretical basis for the structural design and safe operation of underground reservoir dams.